PERAN KOMPETENSI, INDEPENDENSI DAN PENGALAMAN TERHADAP KUALITAS AUDIT - Yogantara, Komang Krishna; Asana, Gde Herry Sugiarto; Laksminingsih, Luh Gede Made (Program Studi Akuntansi Fakultas Ekonomi Universitas Mahasaraswati Denpasar, 2018)
The purpose of this study is to find the influence of competence , independence of , experience and ethics auditor on the quality of audit .As for population in research it is a whole auditor the office public accountant se-bali which consisted of 88 auditor to technique the sample collection using a technique probability of sampling that is simple random sampling. Independent variÂable the research is competence, independence, experience and ethics auditors and variable dependennya is the quality of the audit.For methods data collection was carried out by using a questionnaire and testing hypothesis done by using analysis of multiple regression.Based on the results of the conducted then we can conclude that both a partial simultaneous and compeÂtence, independence, experience and ethics auditors it has some positive effects on the quality of audit.